2019
DOI: 10.1177/0163443719846613
|View full text |Cite
|
Sign up to set email alerts
|

Gaining trust: the articulation of transparency by You Tube fashion and beauty content creators

Abstract: This article proposes a new typology of transparency markers in fashion and beauty You Tube videos. It looks at how online content creators disclose the process of selecting and featuring products in their videos and analyses their discursive performance of transparency. It argues that these content creators employ a mix of routines of transparency, authenticity and independence, which they perform simultaneously, constructing themselves as trustworthy. The article suggests that, although restricted in both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
0
29
0
2
Order By: Relevance
“…However, findings (Trivedi 2018 ) suggest that attractive celebrity influencers have a greater influence on consumers’ reactions in the fashion and lifestyle industries than generalist influencers. In addition, this study reported that general public influencers in the cosmetics field had a greater influence on consumers than celebrities did (Choi & Behm-Morawitz 2017 ; Dekavalla 2019 ). Therefore, the first hypothesis of this study is as follows:…”
Section: Literature Reviewmentioning
confidence: 83%
See 1 more Smart Citation
“…However, findings (Trivedi 2018 ) suggest that attractive celebrity influencers have a greater influence on consumers’ reactions in the fashion and lifestyle industries than generalist influencers. In addition, this study reported that general public influencers in the cosmetics field had a greater influence on consumers than celebrities did (Choi & Behm-Morawitz 2017 ; Dekavalla 2019 ). Therefore, the first hypothesis of this study is as follows:…”
Section: Literature Reviewmentioning
confidence: 83%
“…In some studies that have investigated influencer marketing, influencers were classified as information providers. SMIs who engage in the cosmetic industry are called beauty creators, and influencers in the social media environment are called information providers (Choi & Behm-Morawitz 2017 ; Dekavalla 2019 ). Different types of beauty influencers have different effects on consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authenticity expectations were also about disclosing sponsored collaborations using tactics that increased audiences' trust (Dekavalla, 2019). Reflecting ongoing debates about journalism's market orientation (Hanitzsch, 2007), these notions go to the heart of questions of autonomy, and the need to disclose potential economic influences.…”
Section: Discussion: Implications For Boundary Workmentioning
confidence: 99%
“…Исследователи анализируют, как создатели контента в социальных медиа конструируют свою экспертную позицию, при помощи чего добиваются доверия аудиторий. Среди сфер, которые становятся предметом изучения, лайфстайл-блогинг, модные и бьюти-практики [Bhatia, 2018;Dekavalla, 2020;Tolson, 2010], активизм [Allgaier, 2020;Laaksonen, Pantti, Titley, 2020], «алгоритмическая экспертиза», то есть рекомендации по продвижению контента на онлайн-платформах [Bishop, 2020], и другие. Чаще всего об экспертизе говорят применительно к естественнонаучному знанию и связанным с этим темам (например, питание, вакцинация, климат), а гуманитарному знанию, и в частности истории, уделяется мало внимания.…”
Section: экспертное знание офлайн и онлайнunclassified